The activity of cell-free supernatant of Lactobacillus crispatus M247: a promising treatment against vaginal infections - Giulia Santarelli; Roberto Rosato; Michela Cicchinelli; Federica Iavarone; Federica Iavarone; Andrea Urbani; Andrea Urbani; Maurizio Sanguinetti; Maurizio Sanguinetti; Giovanni Delogu; Giovanni Delogu; Flavio De Maio (Frontiers in Cellular and Infection Microbiology)
Lactobacillus crispatus is renowned for its antimicrobial properties, and some strains are used to treat vaginal dysbiosis, although the mechanisms underlying the antimicrobial properties remain elusive. We isolated L. crispatus M247 (LcM247) from a commercially available probiotic product Crispact® and tested its antimicrobial activity against selected pathobionts such as Escherichia coli, Klebsiella pneumoniae, Staphylococcus aureus, Streptococcus agalactiae, Enterococcus faecalis and Candida albicans using both cocultures and testing the antimicrobial activity of cell-free supernatant (CFS) obtained from the culture of the probiotic strain. Furthermore, we demonstrate that CFS antimicrobial activity is pH dependent and that it is not affected by temperature and proteinase K treatment. Proteomic analysis suggests that this activity is mediated by S-layer secreted proteins. In a series of in vitro infection models, we infected Henrietta Lacks’ cervical eukaryotic cancer cells (HeLa) with E. coli, S. agalactiae and C. albicans at specific multiplicities of infection (MOIs) before the administration of LcM247, CFS, gentamicin or fluconazole alone or in combination with LcM247/CFS. We observed a slight decrease in the microbial burden following LcM247 administration, while treatment with CFS significantly reduced microbial growth compared to control and antimicrobial compounds. These results highlight the antimicrobial properties of LcM247 and its CFS and the likely mechanism of action that contributes to the eradication of common pathobionts. We show that actively replicating LcM247 is less efficient than its CFS, so the oral administration of LcM247 may result in treatment failure. Finally, the use of CFS may result in an upswing of the host Lactobacillus strains and promote the engraftment of Lactobacillus probiotic treatments.